2013
DOI: 10.1016/j.gynor.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Novel TP53 gene mutation and correlation with p53 immunohistochemistry in a mixed epithelial carcinoma of the endometrium

Abstract: ► We examine the correlation between p53 immunohistochemistry and TP53 gene mutation status in a mixed epithelial endometrial carcinoma. ► We describe a novel R306* (c.916C > T) mutation in exon 8 of the TP53 gene. ► We propose that the distinction between Type I and Type II endometrial carcinomas may be more fluid than previously believed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Analysis of a low-hypodiploid xenograft containing the p.Arg306 Ã mutation identified elevated TP53 expression (Holmfeldt et al 2013). This mutation was also identified in a case of endometrioid adenocarcinoma, in which the mutation was present only within the serous component of a mixed epithelial carcinoma, and was accompanied by elevated TP53 expression in serous, but not endometrioid cells in the tumor (Sholl et al 2012). Moreover, the p.Gly302fs HYPO052) that was originally reported as an aberrantly spliced isoform was later found to contain an 8.7-kb focal deletion of exon 2 -exon 5 on deeper sequencing analysis (Holmfeldt et al 2013).…”
Section: Tp53 Alterations In Hypodiploid Allmentioning
confidence: 76%
“…Analysis of a low-hypodiploid xenograft containing the p.Arg306 Ã mutation identified elevated TP53 expression (Holmfeldt et al 2013). This mutation was also identified in a case of endometrioid adenocarcinoma, in which the mutation was present only within the serous component of a mixed epithelial carcinoma, and was accompanied by elevated TP53 expression in serous, but not endometrioid cells in the tumor (Sholl et al 2012). Moreover, the p.Gly302fs HYPO052) that was originally reported as an aberrantly spliced isoform was later found to contain an 8.7-kb focal deletion of exon 2 -exon 5 on deeper sequencing analysis (Holmfeldt et al 2013).…”
Section: Tp53 Alterations In Hypodiploid Allmentioning
confidence: 76%
“…It has been demonstrated that the prognosis gets worse even in the existence of very small amounts of type 2 components in stage 1 endometrial cancer and should be considered as high grade 17 . In addition to studies showing that the prognosis for the presence of a serous component is similar to pure serous carcinomas 8,18 , there are studies showing that prognosis of the MECs are better than that of pure serous carcinomas [14][15][16]19,20 . Rossi et al 20 drew attention to the high grade of endometrioid component for MEC in their study and suggested that they were likely to be considered more as pure type II carcinomas than MEC.…”
Section: Discussionmentioning
confidence: 99%